2011
DOI: 10.1007/s10661-011-1901-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of flubendiamide in/on Brinjal (Solanum melongena) fruits

Abstract: A field experiment was conducted at Anand Agricultural University, Anand during Sept-Dec, 2009 to study the rate of degradation of flubendiamide in/on brinjal fruits following foliar application of Fame 480 SC at 90 (standard dose) and 180 (double dose) g a.i. ha( -1). The residues estimated using HPLC revealed persistence of flubendiamide in/on brinjal till 3rd and 7th day after the last spray at standard and double dose, respectively. The residues of flubendiamamde were reported as parent compound, and no de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Similar results were reported in cabbage (Mohapatra et al 2010) and in brinjal (Chawla et al 2011) and in tomato (Paramasivam and Banerjee 2012). The Paramasivam and Banerjee (2011).…”
Section: Persistence Of Flubendiamide On Tomato Fruitssupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were reported in cabbage (Mohapatra et al 2010) and in brinjal (Chawla et al 2011) and in tomato (Paramasivam and Banerjee 2012). The Paramasivam and Banerjee (2011).…”
Section: Persistence Of Flubendiamide On Tomato Fruitssupporting
confidence: 85%
“…The half-life values of flubendiamide on brinjal were observed to be 0.62 and 0.54 days, respectively, following three applications of flubendiamide 480 SC at 90 and 180 g a.i.ha −1 on brinjal fruits (Takkar et al 2012). Similarly, the half-lives of flubendiamide were reported to be 2.68 and 2.55 days following application of flubendiamide at 90 and 180 g a.i.ha −1 on brinjal fruits (Chawla et al 2011).…”
Section: Persistence Of Flubendiamide On Tomato Fruitsmentioning
confidence: 91%
“…Studies have reported the dissipation and dietary risk assessment of CAP and FBD in various plant samples, including brinjal, kale, paprika, perilla leaves, strawberries, tea leaves, and tomatoes [ [8] , [9] , [10] , [11] , [12] , [13] ]. Pesticide residue levels can vary significantly depending on whether the crops are grown in a greenhouse or in open fields.…”
Section: Introductionmentioning
confidence: 99%
“…gas chromatographynitrogen phosphorous detector (GC-NPD), gas chromatography-flame photometric detector (GC-FPD) 6 , gas chromatography-mass spectrometry (GC-MS) 21,22 , highperformance liquid chromatography (HPLC) 9 , liquid chromatography-mass spectrometry (LC-MS) 23 ; flubendiamide, viz. high-performance liquid chromatography ultraviolet (HPLC-UV) 9,10 , high-performance liquid chromatography photodiode array detector (HPLC-PDA) 24 , high-performance liquid chromatographyelectrospray ionisation-tandem mass spectrometry (HPLC-ESI-MS/MS) 13 , high-performance thin-layer liquid chromatography (HPTLC) 25 , and LC/MS 25 , and imidacloprid, viz. by thin-layer chromatography (TLC) 26 , HPLC 27 and GC-MS 28 .…”
mentioning
confidence: 99%